Subscription Publishing and the Booktrade in the Eighties: The Invasion of Ontario - Brodie, Alexander H. (Studies in Canadian Literature, 1977)
Nineteenth-century subscription publishing, an overlooked aspect of Canadian publishing history, led to the establishment of a once-vigorous Canadian publishing industry which might be said to constitute in many respects the germ of Canada's twentieth-century publishing structure. An investigation reveals post-Confederation marketing by US publishers who avoided tax duties under the disguise of Canadian imprints based in smaller population centres such as Paris, Ontario or London, Ontario. The 1897 Duties of Customs Act ended the import of these reading materials and led to the increased licensing of US publishers, integrating them into the Canadian publishing scene and its normal trade channels.